Impact of “trash TV” on children and adolescents´ mind and behavior - Arboccó de los Heros, Manuel (2012)
In the next job it reflects on the negative impact that generates the bad use of television in our environment and in other countries of the world. We will review its use and abuse, and the phenomenon of the “trash TV” as one of the factors favoring a number of shortcomings in the mind and the conduct of persons, in particular children and adolescents. A series of important research and conclusions reached by specialists in the area will be remembered and we raise a series of recommendations to try to stop damage already under way.